Sincronía reproductiva interpoblacional de Agave cocui (Agavaceae) en Venezuela - J. Figueredo, Carmen (Universidad de Costa Rica, 2011)
Agave cocui (Agavaceae) is a species with broad distribution in arid and semiarid areas of Venezuela and Colombia. Despite of its ecological importance as a source of food for wildlife, and its economic value for production of a spirit drink, studies on the reproductive ecology of the species are relatively rare. In this study, we conducted a oneyear evaluation of the flowering and fruiting phenology of A. cocui in the eight representative localities of the species? distribution in Venezuela. Within each study site, we chose an area with a minimum of 50 reproductive individuals and followed their reproductive phenophases with the help of binoculars, using six qualitative cathegories (emerging reproductive stalk, flowers, inmature fruits, mature fruits, bulbils and dry stalk) every two months. Emergence of the reproductive stalk in most of the examined populations began in September (rainy season), although this event delayed two months in a few populations. We detected significant negative correlations between precipitation and the percentage of flowering occurrence in four of the eight populations. Floral resources are available for flower visitors during approximately five months of the year (January-May). In most populations production of flowers initiated in January (dry season), and for Western Venezuela and Andean regions, the flowering main peak occurred in January. Localities from the Central and Eastern Coast exhibited the flowering peak in March, showing a delay of approximately two months with respect to other populations. Beginning of fruit set varied among localities from January to May; however, peak production of mature fruits concentrated in May, and fruit occurrence varied broadly between 5.2 and 85%. Bulbil production was detected in all populations and varied greatly among them (maximum percentage per population: 26.19-92.10%). High flowering synchronicity (Phenophase Overlapping Index: 0.756 and 0.999) was observed among all populations monitored in Western Venezuela, including the Andean localities. This condition might facilitate the existence of a nectar corridor from the Western Coast and nearby islands, to the Andean arid patches, which could be potentially used by nectar-feeding bats and birds dependent on agave flowers during part of the year.